[Un]Forgetting History: Preparing Public Health Professionals to Address Structural Racism. (January 2022) - Rosario, Carrie; Al Amin, Saif; Parker, Cedric
Abstract : Context: Structural racism, a fundamental cause of health inequities, must be dismantled to fulfill society's interest in ensuring conditions in which all people have opportunities conducive to health. Correspondingly, the Ten Essential Public Health Services center equity, and Council on Education for Public Health (CEPH) accreditation criteria require public health students to learn about racism. However, little guidance is provided to help faculty empower future generations of public health professionals to challenge it. Program: In response to the 2020 murders of George Floyd, Ahmaud Arbery, and Breonna Taylor, faculty at UNC Greensboro denounced racism and recommitted to anti-racist pedagogy and praxis. In this article, we discuss integrated ways a graduate-level public health assessment and planning course empowered students to name structural racism, understand how it operates, and collaborate for action. Implementation: Specifically, we highlight (1) our use of the book The Color of Law as means to understand racism as a structural intervention; (2) the Harvard Case Teaching Method as an organizing framework to make the classroom a critically engaged democratic setting; (3) change experts from local health and nonprofit organizations engaged in policy making to address social determinants and disparities resulting from structural racism (eg, housing, health care access, food insecurity); and (4) engagement with a minority-owned nonprofit to allow for practice applying knowledge and skills to address local inequities. Discussion: Our 4-pronged pedagogical approach provides an innovative, tangible example for other public health programs as they reflect upon academic institutions' unique power and role in addressing the public health crisis of structural racism.